PENGARUH TUNJANGAN KINERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA ASN DI BALAI DIKLAT INDUSTRI YOGYAKARTA KEMENTRIAN PERINDUSTRIAN - Wahyudi, Harman Is; Insiatiningsih, Insiatiningsih (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2025)
This studies are carried out to decide the impact of performance allowances, painting motivation, and work surroundings on the performance of the National Civil Apparatus (ASN) at the Yogyakarta business training center of the Ministry of Enterprise. worker performance is first-rate, and the amount of work consequences carried out by way of an employee in performing their duties consistent with the responsibilities assigned to them. The factors influencing performance are the surroundings, the internal business enterprise, and employees. The research pattern consisted of 30 civil servants at the Yogyakarta industrial training center, gathered through the distribution of questionnaires using more than one linear regression evaluation technique. The research outcomes show that: (1) performance allowanceshave a high quality and great effect on overall performance; (2) Motivation has a fine and considerable effect on employee performance; (3) The paintings surroundings has a nice and giant effect on worker overall performance; (4) Renumeration, motivation, and the work environment have a effective and giant effect. employees at the industrial education middle in Yogyakarta can be influenced using renumeration variables, work motivation, and work surroundings, at the same time as the remainder is encouraged by different variables outside the have a look at.